AN INTERVIEW WITH MARILISA SHIMAZUMI: LEARNER CORPORA AND THEIR INTERFACES WITH LANGUAGE TEACHING. - Shimazumi, Marilisa; de Lima-Lopes, Rodrigo Esteves (Trabalhos em Lingüística Aplicada, 2025)
In this interview, Dr. Marilisa Shimazumi provides a glimpse into her academic career, which has been closely associated with the use of learner corpora and English language teaching since the 1980s. The interview begins by discussing her training as a researcher, covering her experiences in national and international research projects. The interview also provides information about her current research projects, applying Multidimensional Analysis to learner corpora and the production of language models. Her studies also investigate differences between human and LLMS-generated texts. In her final assessment of the field, she values interdisciplinary collaborations and sees a promising expansion of the field in Brazil.